2017
DOI: 10.3389/fneur.2017.00472
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia Type 2: Clinicogenetic Aspects, Mechanistic Insights, and Management Approaches

Abstract: Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant cerebellar ataxia that occurs as a consequence of abnormal CAG expansions in the ATXN2 gene. Progressive clinical features result from the neurodegeneration of cerebellum and extra-cerebellar structures including the pons, the basal ganglia, and the cerebral cortex. Clinical, electrophysiological, and imaging approaches have been used to characterize the natural history of the disease, allowing its classification into four distinct stages, with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 118 publications
2
90
0
Order By: Relevance
“…SCA2 is characterized by a progressive cerebellar syndrome accompanied by severe saccadic slowing, peripheral neuropathy, autonomic disturbances, pyramidal signs, cognitive disorders, and sleep disturbances . Similar to other SCAs caused by the polyglutamine domain, the onset of SCA2 cerebellar syndrome is significantly controlled by the mutation size and is preceded by prodromal manifestations up to more than a decade before disease onset …”
mentioning
confidence: 99%
“…SCA2 is characterized by a progressive cerebellar syndrome accompanied by severe saccadic slowing, peripheral neuropathy, autonomic disturbances, pyramidal signs, cognitive disorders, and sleep disturbances . Similar to other SCAs caused by the polyglutamine domain, the onset of SCA2 cerebellar syndrome is significantly controlled by the mutation size and is preceded by prodromal manifestations up to more than a decade before disease onset …”
mentioning
confidence: 99%
“…To our knowledge, ours is only the second report of SCA3 in this region, the first being by Gwinn-Hardy et al,11 who described genetic diagnosis of SCA3 in a family residing in the UK and USA following immigration from Antigua. Apart from a cluster of families with SCA2 documented in the Holguin province of Cuba1214 and a cluster of families on Martinique,15,16 there have not been any other reports of any of the SCAs in the Caribbean region.…”
Section: Discussionmentioning
confidence: 91%
“…This phase is followed by the prodromal or preclinical stage, characterized by unspecific neurological features such as painful muscle cramps, sensory abnormalities, subtle cerebellar manifestation (increase of the sway during tandem gait), cognitive decline, autonomic disorders, olfactory dysfunction and hyperreflexia. Electrophysiological studies showed the reduction of the maximal saccadic velocity, REM sleep disorders, increased central motor conduction time in transcranial magnetic stimulation and peripheral sensory axonal damage according of the peripheral nerve conduction studies [3,24]. …”
Section: Lecture Highlightsmentioning
confidence: 99%
“…This stage also allows identification of the best moment to initiate therapies, and identification of sensitive outcome measures [24]. …”
Section: Lecture Highlightsmentioning
confidence: 99%